Reticulocyte haemoglobin equivalent (RET-He): Establishing reference interval and comparison of RET-He Cut-Off value in iron deficiency anaemia and anaemia in chronic kidney disease / Ermi Neiza Mohd Sahid - Ermi Neiza, Mohd Sahid (2016)
Iron deficiency anaemia is the most common cause of anaemia in the general population. The red cell parameters such as mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and conventional laboratory test such as serum ferritin, transferrin and transferrin saturation are widely used in diagnosis of iron deficiency anaemia. However, in chronic kidney disease patients, complication of anaemia particularly in dialysis patient is not easily defined by those conventional tests. During iron replacement and human recombinant erythropoietin therapy, the target haemoglobin level with appropriate ferritin level need to be standardised as to achieve the optimum result while avoiding the risk of iron over load. The problem with many conventional tests is inaccuracy in measuring iron deficiency anaemia due to interference of value by acute phase protein. Recently, the usage of new reticulocyte parameter, Reticulocyte Haemoglobin Content (CHr) was proven to be able to reflect iron availability especially in chronic kidney disease and recognised as a reliable marker in defining functional iron deficiency. CHr analysis was performed using ADVIA 120 and 2120 (Siemens Healthcare Diagnostics, Tarrytown, New York U.S.A) haematology analyser based on flowcytometry principle and recently recommended in several guidelines including National Kidney Foundation (NKF) - Kidney Disease Outcomes Quality Initiative (KDOQI) and NICE Guidelines for Anaemia Management in Chronic Kidney Disease (CKD). In British Guidelines for Laboratory Diagnosis of Functional Iron Deficiency, CHr is one of the recommended tests with a proposed cut-off value of CHr <29 pg for the diagnosis of functional iron deficiency (FID) in patients receiving erythropoiesis-stimulating agents (ESA) therapy.9 Subsequently, a more novel reticulocyte parameter, Reticulocyte Haemoglobin Equivalent (RET-He) was recently introduced which also uses the principle of flowcytometry in its measurement and has been studied to have parallel function comparable to CHr. RET-He is available in the Sysmex XE and XN series hematology analysers (SYSMEX Corporation, Kobe, Japan). RET-He value <25 pg is suggestive of classical iron deficiency and also predicts FID in those receiving ESA therapy.1 The aims of our study were to establish reference interval for RET-He and to assess its diagnostic performance in the detection of iron deficiency in anaemia study population as well as detection of functional iron deficiency in chronic kidney disease patients. Validation of reference interval for RET-He was done in 89 normal subjects and the results show values of 27.0 - 35.9 (pg). The ROC analysis of iron deficiency anaemia study revealed that by using a RET-He cut-off level of 26.6 (pg), iron deficiency could be diagnosed with a sensitivity of 90.53% and a specificity of 92.45%. For functional iron deficiency study in chronic kidney patients, our study show a less favourable result with the cut-off level of RET-He obtained was 29.6 (pg) with sensitivity and specificity of 50% and 68.3% respectively. In conclusion, RET-he proved to be a reliable marker of cellular haemoglobin content and can be used to accurately identify iron deficiency. Keywords: Reticulocyte Haemoglobin Equivalent (RET-He), reference intetvet, iron deficiency anaemia, functional iron deficiency.